1989
DOI: 10.2307/3430740
|View full text |Cite
|
Sign up to set email alerts
|

Multistep Process of Squamous Differentiation in Tracheobronchial Epithelial Cells In Vitro: Analogy with Epidermal Differentiation

Abstract: The lung, in particular the bronchial epithelium, is a major site for tumor formation in humans. Environmental factors, such as cigarette smoke, in conjunction with genetic factors are important determinants in this disease. Malignant cells exhibit alterations in their control of proliferation and differentiation. It is believed that the acquisition of defects in the regulation of these processes is important in the process of carcinogenesis. A clear insight into the basic mechanisms of the regulation of proli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

1990
1990
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 82 publications
(122 reference statements)
0
19
0
Order By: Relevance
“…Some of the cells that we have analyzed were isolated from nonsquamous epithelium (trachea). However, the capacity of human respiratory cells to undergo squamous differentiation in vivo is well known, in response to toxic or mechanic injury or deregulated proliferation . Interestingly, all primary cells, including the trachea, underwent squamous differentiation in culture in the presence of serum and growth factors that hyperactivated the cell cycle.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some of the cells that we have analyzed were isolated from nonsquamous epithelium (trachea). However, the capacity of human respiratory cells to undergo squamous differentiation in vivo is well known, in response to toxic or mechanic injury or deregulated proliferation . Interestingly, all primary cells, including the trachea, underwent squamous differentiation in culture in the presence of serum and growth factors that hyperactivated the cell cycle.…”
Section: Discussionmentioning
confidence: 99%
“…However, the capacity of human respiratory cells to undergo squamous differentiation in vivo is well known, in response to toxic or mechanic injury or deregulated proliferation. 3,37 Interestingly, all primary cells, including the trachea, underwent squamous differentiation in culture in the presence of serum and growth factors that hyperactivated the cell cycle. Skin grafts are used in oncologic surgery for tissue reconstruction in the trachea or esophagus, 5-8 thus indicating the mutual plasticity of these epithelia.…”
Section: Discussionmentioning
confidence: 99%
“…However, these experiments also showed that, of the pre-plateau phase cultures, those with the highest cell density were the least TGFpl responsive. Our interpretation is that the decrease in TGFpl responsiveness may be related to the commitment of increasing numbers of cells to terminal differentiation, which begins to occur spontaneously as tracheal cell cultures enter the second half of the exponential growth phase Jetten, 1989). We recently demonstrated that this process occurs at a n accelerated rate in cultures seeded with a higher density of clonogenic cells (Gray et al, 1991).…”
Section: Discussionmentioning
confidence: 96%
“…Multilayering has been shown in other studies using normal bronchial epithelium (Paquette et al, 2003) and could be attributed to the culture media that are formulated to promote proliferation and inhibit differentiation. Some have suggested that retinoic acid may inhibit the skin‐like morphology of bronchial epithelium (Jetten, 1989; Sachs et al, 2003) and might be necessary for ciliary and mucous cell development (Gray et al, 1996; Koo et al, 1999). While we were successful in obtaining ciliogenesis using the current medium formulation, future modifications of the medium such as switching to a more basal media at late time points, or performing xenograft studies may result in different outcomes.…”
Section: Discussionmentioning
confidence: 99%